2022
DOI: 10.3389/fendo.2021.778984
|View full text |Cite
|
Sign up to set email alerts
|

Primary Adrenal Lymphoma: Two Case Series From China

Abstract: ObjectivePrimary adrenal lymphoma (PAL) is a rare form of adrenal mass. We summarize our experience in its clinical presentation, biochemical indexes, radiological features, pathological information, therapy regimens, and outcomes.MethodsThis was an institutional review board-approved retrospective review of medical records and surgical pathology specimens of patients with a diagnosis of PAL at the Chinese People’s Liberation Army General Hospital and the First Affiliate Hospital of Xiamen University between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(50 reference statements)
0
5
0
Order By: Relevance
“… 22 A retrospective study of 26 patients with primary adrenal lymphoma (which is the largest on this disease we identified in 2022) showed that 81% of subjects had suffered bilateral spreading and 63% of them developed AD. 23 …”
Section: Resultsmentioning
confidence: 99%
“… 22 A retrospective study of 26 patients with primary adrenal lymphoma (which is the largest on this disease we identified in 2022) showed that 81% of subjects had suffered bilateral spreading and 63% of them developed AD. 23 …”
Section: Resultsmentioning
confidence: 99%
“…Bilateral adrenal involvement may also lead to adrenal insufficiency in affected individuals. Higher LDH and β2-microglobulin levels in the biochemistry tests imply the diagnosis of adrenal lymphoma; in contrast, the adrenal CD is usually unilateral with no definitive biochemical abnormalities ( 42 , 43 ). An adrenal puncture biopsy can be considered in cases where a definitive diagnosis cannot be made based on imaging and clinical features ( 25 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are less than 300 cases described in the English literature to date. The information on this entity is still limited to case reports and a few case series reported from India [12], China [2,[13][14][15], Europe, and North America [16]. There were only four PAL cases previously reported from Saudi Arabia, and all were NHL [5][6][7][8] and their clinicopathological data are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%